Covid-19 impact on Church Society Ministry - I Putu Ayub Darmawan; Nasokhili Giawa; Katarina; Sabda Budiman (International Journal of Humanities and Innovation (IJHI), 2021)
The ongoing COVID-19 pandemic has caused countless impacts and influences on human life. It disturbs the order of life and macro and micro-economics, drastically and radically changes human cultural and behavioral patterns, and greatly impacts the concepts of church theology, pastoring, and ministry. This study is a descriptive qualitative study on the COVID-19 and normal & abnormal reactions & responses to it. Through this article, the authors observed that the COVID-19 existence has transformed and recorrected the Christian paradigm on 1) ecclesiology, which to date exclusively based on building to the real Church, namely God’s people in the form of house/“tent” churches; 2) digital media utilization in this Society 5.0 era as God’s grace to all humanity. Findings and changes in society through renewable technology are an inseparable part of the pandemic. A dichotomic gap of understanding between science and technology for centuries should be reformulated. New technological inventions and social media created by humans are media in the hands of God that should be utilized by the Church to minister in various categories to improve the quality of ministry and service; and 3) creative and innovative interpretation of threefold responsibilities of the Church: koinonia, diakonia, and martyria.